Benedyktyńskie sympozjum patrystyczne - Wolak, Halina (Vox Patrum, 1981)
Report from the national Patristic Symposium, which took place September 2-23, 1980 in Wrocław and was dedicated to the person and the Rule of Saint Benedict.